PENGARUH RANSOMWARE DAN PHISHING TERHADAP TINGKAT PEMAHAMAN MAHASISWA FAKULTAS EKONOMI BISNIS TENTANG KEJAHATAN SIBER - Siahaan, Gelora Chita; Aminah, Aminah (Gapenas Publisher, 2025)
This study aims to identify the level of understanding of FEB UBL students regarding ransomware and phishing threats, as well as to determine the extent of students' preparedness in facing such attacks. This study applies a quantitative method by utilizing primary data collected through questionnaires. The study population consists of 225 students from the Faculty of Economics and Business, Class of 2021, who have completed their final projects. The sample selection used the Slovin formula at 10%, resulting in 70 respondents. The analysis concluded that ransomware and phishing significantly influence students' understanding of cybercrime.